Performance analysis of undoped and Gaussian doped cylindrical surrounding-gate MOSFET with it's small signal modeling. (November 2016) - Sood, Himangi; Srivastava, Viranjay M.; Singh, Ghanshyam
Abstract: The scaling of the solid-state devices are reaching its limit and it enhances the significant short channel effects. To overcome these problems, the surrounding-gate MOSFET is emerging as a promising structure and is a replacement of traditional MOSFETs. In this research work, authors have analyzed the performance of various parameters for the cylindrical surrounding-gate MOSFET using surface potential based approach and further transformation of variable technique to find the solution of the same differential equation. However, the modeling of terminal charge and trans-capacitance are also presented which is used for the circuit simulation. The influence of Gaussian doping (in vertical direction across the radius of the device) has been analyzed and solution of the surface-potential is derived based on the taylor series expansion. Highlights: It is a structure of Silicon pillar surrounded by the gate in a cylindrical fashion. Cylindrical surrounding-gate MOSFET and equivalent circuit process has been analysed. Drain current, ON-resistance and transcapacitance and conductance has been presented. Improved results accomplished for cylindrical structure MOSFET has been realized. The S-parameters can be evaluated using the network analysis over the THz regime.